p.Gly743Val Mutation in COL4A1 Is Responsible for Familial Porencephaly and Severe Hypermetropia - Scoppettuolo, Pasquale; Ligot, Noémie; Wermenbol, Vanessa; Van Bogaert, Patrick; Naeije, Gilles (Frontiers in Neurology, 2020)
COL4A1 is an essential component for basal membrane stability. Exon mutations of the COL4A1 genes are responsible for a broad spectrum of cerebral, ocular, and systemic manifestations. We describe here the phenotype of a likely pathogenic gene variant, p.Gly743Val, which is responsible for a missense mutation in the COL4A1 gene exon 30 in a three generation family with severe hypermetropia and highly penetrant porencephaly in the absence of systemic manifestations. This report highlights both the broad spectrum of COL4A1 mutations and the yield of testing the COL4A1 gene in familial ophthalmological and brain disorders.